Cystic Cervical Lymphangioma in children: OK-432 therapy - Falcón, Ramón Terré (2008)
The treatment of cervicofacial lymphangioma has been changing in recent years, and in this process intralesional injection of OK-432 has been proposed as an effective treatment of lymphangioma for patients of all ages. We are reporting on a cervical cystic lymphangioma in a girl aged 11, treated with an intra-lesion injection of 20 cc with 0,01 mg/cc dilution of OK-432 in physiological serum. Sole complications were fever and local reaction where the solution was injected, and cosmetically the outcome was excellent, leaving no lesions on the skin at the injection site, unlike other sclerosing agents. One month after treatment the lymphangioma had totally remitted and fourteen months later continues in remittance.